Playing Mas': The Construction and Deconstruction of National Identity in the Trinidad Carnival - de, Freitas Ann Patricia (My University, 1994)
Annually, between the Christian seasons of Christmas and Lent, Trinidadians devote themselves to island-wide Carnival activities. A season in itself, the Carnival period culminates in a two-day street celebration marked by music, dancing and masquerade performances. For many Trinidadians, Carnival is the quintessential expression of Trinidadian-ness. On one level, this thesis is an ethnographic "enactment" of one particular Carnival celebration in the circumscribed space and time of Port of Spain 1992. On another, this study explores the historical, systemic, political and hermeneutical linkages between Trinidad's "national" identity, its culture and its annual Carnival. I argue that Trinidad's Carnival is more properly understood, not as a rite of reversal, but as a performance which constitutes and expresses the Trinidadian Self. For many Trinidadians, Carnival time is not the-world-turned-upside-down, but the-world-turned-right-side-up. An embedded argument in my thesis is a critique of discourses of identity which assume the oppositional categories of a unified Self over and against a distinctive Other. This distinction is found not only in the specific case of Trinidad's Carnival, but in all analyses of cultural identity, and in the anthropological endeavour itself. I show how the modern Carnival, as the dominant "national" icon of Trinidadian identity, subverts the very ideal of a "national" identity it is meant to create and reinforce. Based on fourteen months of fieldwork in Trinidad, I present multiple views and experiences of the Trinidad Carnival. These representations are situated within the theoretical frameworks provided by both academic Euro-American anthropology and the multiple discourses honed in Trinidadian rumshops, yards, homes, media depictions and academia. Carnival is examined in order to open up new spaces for the re-articulation of identity and a reconstituted politics of difference.
Keywords: Anthropology; Anthropology